Demystifying the International Criminal Court (ICC) Target Africa Political Rhetoric - Torque Mude (Scientific Research Publishing, 2023)
The ongoing debate on the ICC’s selective application of international criminal law targeting Africans has had negative implications on the international court and the law it applies. As a consequence of the political rhetoric that the ICC targets Africa, African leaders and their sympathisers have tended to view the court with contempt and some have expressed intentions to withdraw their membership of the court. Against this background, this paper examines the argument that the ICC targets Africa which amounts to an affront to international criminal law and its objective to end impunity to achieve international justice. The conclusion drawn from this study is that the assertion that the ICC targets Africa is a mere political rhetoric that warrants demystification. It is a political rhetoric advanced by African leaders to manipulate their way out of the responsibility to be accountable to international criminal law. Furthermore, the notion that the court targets Africans lacks substantive credibility as it ignores several structural and technical underpinnings such as the jurisdictional triggers, the role of the United Nations Security Council (UNSC) and other functional modalities that guide the operation of the court. Data for this paper were gathered from journal articles, organisational reports and documents, newspapers, case reports, treaties and other online sources.